Effect of Centrifugation on Nanoemulsion Stability with Tween, PEG, Poloxamer 188, and Transcutol-p - Fauziah Rahmola; Mohamad Adam Mustapa; Mohamad Aprianto Paneo; Endah Nurrohwinta Djuwarno; Muhammad Taupik (Jurnal Farmasi Teknologi Sediaan dan Kosmetika, 2026)
This study evaluated the effect of centrifugation speed on the physical stability of a nanoemulsion base formulated with grapeseed oil (long-chain triglyceride, LCT) and stabilized using Tween 80–PEG 400, Poloxamer 188, and Transcutol-P, as a preliminary platform for topical and oral pharmaceutical applications. A descriptive–experimental design was employed. Nanoemulsion bases were prepared by the aqueous titration method followed by 60-minute sonication. Four formulations (F1–F4) contained 5% grapeseed oil and 2% Poloxamer 188, while Tween 80/PEG 400 levels and Transcutol-P (0.5–2%) were varied. Accelerated physical stability was assessed by centrifugation at 2000, 4000, 6000, and 8000 rpm for 30 minutes, followed by organoleptic observation, emulsion type determination, pH measurement, and viscosity testing. All formulations remained visually stable at 2000 rpm. At 4000 rpm, F1–F2 showed increased turbidity with a thin top layer (incipient creaming), whereas F3–F4 remained stable without phase separation. At 6000 rpm, F1–F2 became more turbid with the onset of a surface oil layer, while F3–F4 maintained stability. At 8000 rpm, F1–F2 exhibited complete phase separation; F3 showed a slight oil layer; and F4 was the most stable, showing only minimal turbidity without total phase breaking. All formulations were classified as oil-in-water (O/W). The pH ranged from 6.0 to 7.0 (mean 6.45 ± 0.42) and viscosity from 176 to 220 cP (mean 196.25 ± 18.89). In conclusion, increasing centrifugation speed effectively differentiated formulation robustness, with F4 demonstrating the highest resistance to mechanical stress up to 8000 rpm.